Wrongful Conviction as Racialized Cumulative Disadvantage - Umamaheswar, Janani (The British journal of criminology, 2023)
Despite a growing body of scholarship on wrongful convictions, research on the prison and pre-prison experiences of wrongfully-convicted men (including the racialized nature of these experiences) continues to be limited. In this article, I draw on in-depth interviews with 15 exonerated men in the United States to frame wrongful conviction as an experience of racialized cumulative disadvantage, defined as the accrual and perpetuation of socioeconomic, psychological, and emotional harms that disproportionately impact Black and Hispanic wrongfully-convicted men over the life course. Through this analysis, I reveal the intersecting and accumulating inequalities that are (re)produced by the processes that generate wrongful convictions and by the experience of wrongful imprisonment. In addition to underscoring the need for critical evaluation of the role of state actors responsible for wrongful convictions, these findings speak to the importance of restorative justice programs to support Black and Hispanic exonerees’ recovery following wrongful imprisonment.